Investigation of highly efficient CO2 hydrogenation at ambient conditions using dielectric barrier discharge plasma - Zhihao Zeng; Yujiao Li; Yunfei Ma; Xiaoqing Lin; Xiangbo Zou; Hao Zhang; Xiaodong Li; Qingyang Lin; Ming-Liang Qu; Zengyi Ma; Angjian Wu (Green Energy and Resources)
The increasing utilization of CO2 for synthesizing high-value fuels or essential chemicals is a potentially effective approach to mitigating global warming and climate change. Compared to thermal catalytic CO2 conversion under harsh operating conditions (400∼500°C, 10 MPa), non-thermal plasma can overcome kinetic barriers and trigger reactions beyond thermal equilibrium at ambient temperature and pressure. In this study, the effects of operating conditions (discharge frequency, input power, and gas flow rate) and geometrical parameters (discharge length, discharge gap, and dielectric materials) have been extensively analyzed using typical cylindrical dielectric barrier discharge (DBD) plasma. The discharge characteristics changed by operating conditions (including waveforms of applied voltage and current) are compared, indicating higher applied voltage and lower gas flow rate can strengthen the filamentary discharges. The results demonstrate CO2 conversion rate increases with the increase of applied voltage and the decrease of CO2/H2 ratio, achieving its maximum value of 43.0% at 20 mL/min. The highest energy efficiency of 3771.9 μg/kJ for CO generation is obtained at the applied voltage of 5.5 kV and gas flow rate of 40 mL/min, respectively. Besides, the structure of plasma reactor also impacts the performance of CO2 conversion. On the one hand, the discharge gap has a significant role in the variation of CO2 conversion and product selectivity, which is attributed to the electric field density and corresponding electron-induced reaction. On the other hand, the circulating water-cooling jacket was used to find out the influence of reaction temperature, which switched the product from CO to CH4. This work will pave the way for a sustainable alternative towards future CO2 conversion and utilization.